Impact Affecting External Debt of Lao Government - PHOUNNALY, Phayvanh; VATTHANA, Mongkhoun (Souphanouvong University Journal Multidisciplinary Research and Development, 2018)
Lao PDR is a least developed country (LDC), the government revenue from tax is limited and inadequate, income level and the saving level of country is low, there is a gap between government spending and revenues from the past to the present, there for, Lao government usually has to borrow external fund to finance the budget deficit, as well as to stimulate growth of Lao economy. To get rid of LDC in 2020. Since the Asia financial crisis of the 1998 Lao government has to spend more to stimulate the economy. As a result, the debt of Laos has risen steadily. This reason make researchers interested to study impact affecting external debt of Lao government. The paper is to study external debt structure and factors that determine the amount of external debt of Lao PDR. Time-series secondary data from Asia Development Bank (ADB) and The Bank of Lao PDR since 1986-2016. This is a descriptive and quantitative study using the econometric model to analyses the relationship between external debt and its determining factors and OLS technique employed as method of analyses. The results of the study shows that external debt structure of the Lao government from 1986 to 2016 are mainly from long-term debt, the ratio of external debt to GDP is over 50.28% every year and the ratio between budget deficit and external debt is less than 10%. It mean that making external debt is to accelerate the development economic structure and to graduate Laos from LDC in 2020. The determining factors are GDP, repayment on external debt and exchange rate. These factors are statistically significance in determining external debt at 99% level of confidence. It mean that an increase of GDP by $1 million would cause external debt increase by $0,615 Million, if increase of repayment by $1 million would cause external debt increase by $ 5.57 Million and increase of exchange rate by 1 kip per dollar would cause external debt increase by $0.186 Million, but budget deficits, international reserves fund and interest rates didn’t determine affecting external debt of Lao government.